2015
DOI: 10.5539/gjhs.v7n4p323
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nursing Students’ Communication Abilities in Clinical Courses in Hospitals

Abstract: Background:Joint Commission on Accreditation of Healthcare Organizations (JCAHO) has established, improving communication as a priority for improving patient safety since 2006. Therefore, the present study aimed to evaluate nursing students’ communication abilities to recognize their strengths and weaknesses in communication skills.Method:This cross-sectional study was carried out in 2014. The study participants included all the nursing students who passed two semesters in Fatemeh School of Nursing and Midwife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 15 publications
3
48
1
7
Order By: Relevance
“…Its score was the highest compared with those of the other domains after intervention in the experimental group. According to the significant role of communication in promoting patient safety (9), training methods of the current study can be applied to improve students' communicative skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its score was the highest compared with those of the other domains after intervention in the experimental group. According to the significant role of communication in promoting patient safety (9), training methods of the current study can be applied to improve students' communicative skills.…”
Section: Discussionmentioning
confidence: 99%
“…The results of a study showed that nursing students needed to improve their communication skills (9). Various efforts are made to acquaint the medical society with teamwork concept and skills as the leading technique to improve the quality of healthcare services among healthcare professionals (10).…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that there was a statistically significant association between socio demographic statuses and knowledge of therapeutic communication. A study in Western Ethiopia reported that there was no statistically significant association between socio-demographic variables and knowledge of therapeutic communication (Thanasekaran et al, 2017 (Shafakhah et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Touch is considered as one of the most powerful form of therapeutic communication and can be explained as bringing the sense of caring by holding a patient's hand, using silence allowing the patient to think & gain some insight into the situation. (Sherko et al2013).Communication skills support in providing information & feedback, giving hope to patient and helping them to cope with anxiety during hospitalization (Shafakhah et al,2015). Nurses could provide a higher patient satisfaction, better health outcomes, quality of treatment care & more active self -management in patients with chronic diseases when they apply therapeutic communication for their patients (Ferreira et al,2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation